Implementation of Muhadharah Program Activities in Self Improvement of Students (Case Study at The Roudlotul Qur'an Lamongan Islamic Boarding School) - Zulfiyatul Firdaus; Siti Latihfatus Sun'iyah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Muhadharah activities are one of the muhadharah programs at the Roudlotul Qur'an Lamongan Islamic boarding school. the muhadharah activity program is one to train students to preach and lecture. not only that, muhadharah activities are activities to train self-confidence. Preliminary studies at Islamic boarding schools show that there are several problems in terms of muhaharah and self-confidence activities at the Roudlotul Qur'an Lamongan Islamic boarding school. Therefore, this research on muhadharah activities and students' self-confidence at the Roudlotul Qur'an Lamongan Islamic boarding school is relevant to do. The purpose of the study was to find out. The results of this study showed that the activities of muhadharah and the confidence of students at the Roudlotul Qur'an Lamongan Islamic boarding school, that: (1) Muhadharah activities were carried out once a week on Sunday nights. It is carried out in their respective complexes, consisting of the Qodim, Jadid, Rijal, Darul Amin complex. In the Darul Amin complex, there are no muhadharah activities because the Darul Amin complex focuses on memorizing the Al-Qur'an. (2) efforts to increase self-confidence from students in carrying out muhadharah activities at the Raudhotul Qur'an Lamongan Islamic boarding school, which is carried out by means of administrators at muhadharah activities always reminding scheduled officers or students to practice preparing their duties according to the division that has been obtained later with support among students and also motivating themselves and providing motivation to other students. (3) inhibiting factors and supporting factors for muhadharah activities, inhibiting factors and supporting factors are divided into two, namely internal and external factors. As for the internal factors, the influence on the individual students includes in terms of the influence of the background of the students who have different personality characteristics .